BENTHIC FORAMINIFERA IN SOUTH WAIGEO WATERS, RAJA AMPAT, WEST PAPUA - Suhartini M. Natsir; M. Subkhan (BULLETIN OF THE MARINE GEOLOGY, 2012)
Waigeo Island is one of four large islands of the Raja Ampat group, West Papua Province. This area lies in the heart of the coral triangle region as the most marine bio-diversity on Earth. Coral reef ecosystem of the Waigeo is a favorable habitat for various organisms including foraminifera. Foraminifera have been proven as useful indicator of water quality surrounding the coral reef environment since FORAM Index was formulated. It gives additional importance of foraminifera beside their common uses on micropalaeontology for petroleum industry and palaeoecology. Therefore, it is very important to obtain data of the benthic foraminifera from various coral reef environments in Indonesia, such as around Waigeo Island. Sediment samples of this study were collected from 12 sites in southern part off Waigeo Island, on July 2011. Observation on benthic foraminifera shows that the study area is dominated by symbiotic bearing benthic foraminifera, Amphistegina lessonii, belongs to Suborder Rotaliina. This occurrence increases the values of FORAM Index (FI) at certain sites. Generally, the values of FI from most sites are high (FI>4) that provide a good indication for reef growth or recovery. The values of FI less than 2 are found at RJ3 and RJ4 indicate stress environment for reef growth and they are dominated by opportunistic and heterotrophic functional groups of Elphidium and Quinqueloculina. Keywords: benthic foraminifera, high value FI, Waigeo Island, West Papua Pulau Waegio merupakan salah satu dari empat pulau besar di Kepulauan Raja Ampat, Provinsi Papua Barat. Wilayah in terletak di jantung segitiga terumbu karang sebagai pusat paling kaya keanekaragaman hayatinya di bumi. Ekosistem terumbu karang Waigeo merupakan habitat yang cocok bagi kehidupan berbagai organisme termasuk foraminifera. Foraminifera telah terbukti sebagai indikator kualitas air sekitar terumbu karang setelah diformulasikan Indeks FORAM. Dengan demikian foraminifera telah mempunyai kegunaan tambahan selain fungsi umum dalam bidang mikropaleontologi pada industri perminyakan dan paleoekologi. Oleh karena itu sangat penting untuk mendapatkan data foraminifera bentik dari ekosistem terumbu karang di wilayah Indonesia, seperti perairan Pulau Waigeo. Sampel sedimen untuk studi ini diambil di 12 titik lokasi sebelah selatan Pulau Waigeo pada bulan Juli 2011. Hasil pengamatan memperlihatkan bahwa daerah penelitian di dominasi foraminifera bentik yang bersimbose dengan terumbu karang, Amphistegina lessonii, anggota Subordo Rotaliina. Kehadirannya meningkatkan nilai FI dari titik lokasi tertentu. Sebagian besar titik lokasi mempunyai nilai FI>4 memberi indikasi bahwa kondisi perairannya kondusif untuk pertumbuhan karang yang terletak di ekosistem terumbu karang. Secara umum, nilai FI di sebagian besar titik lokasi tinggi (>4) yang member indikasi kondisi lingkungan bagus bagi pertumbuhan karang. Nilai FI rendah (